WAYS OF TEACHING THE INTERPRETATION OF AESTHETIC CATEGORY AND THEORETICAL CONCEPTS IN LITERATURE LESSONS - Kambarova, Saodat (Журнал иностранных языков и лингвистики, 2023)
The last decade was characterized by the rapid development of aesthetics and literary science: non-classical categories of aesthetics became the object of research of academic aesthetics; new approaches to the problems of literary theory were formed. In particular, the idea of ​​multiple methods of teaching literature was taught on modern literary theory, the synthesis of the aesthetics of oral creativity, a detailed system of theoretical and historical poetics and concepts, the literary process of the 21st century was perceived in a new way. This article explains that the quality of students’ acquisition of literary-theoretical concepts and aesthetic categories depends on the teacher’s ability to competently organize the process of literary education and manage their acquisition. In addition, the study of interrelated concepts such as "author - work - reader" will contribute to the preparation of the reader with the ability to appreciate the artistic work.